Metabolic profiling of phenolic acids and oxidative stress markers after consumption of Lonicera caerulea L. fruit - Heinrich, Jan; Valentová, Kateřina; Vacek, Jan; Palíková, Irena; Zatloukalová, Martina; Kosina, Pavel; Ulrichová, Jitka; Vrbková, Jana; Šimánek, Vilím (Journal of agricultural and food chemistry, 2013)
This study investigated the effect of one-week consumption of 165 g/day fresh blue honeysuckle berries (208 mg/day anthocyanins) in 10 healthy volunteers. At the end of intervention, levels of benzoic (median 1782 vs 4156), protocatechuic (709 vs 2417), vanillic (2779 vs 4753), 3-hydroxycinnamic (143 vs 351), p-coumaric (182 vs 271), isoferulic (805 vs 1570), ferulic (1086 vs 2395), and hippuric (194833 vs 398711 μg/mg creatinine) acids by LC/MS were significantly increased in the urine. Clinical chemistry safety markers were not altered. Oxidative stress markers, erythrocyte glutathione peroxidase (0.73 vs 0.88 U/g Hb) and catalase (2.5 vs 2.8 μkat/g Hb) activities, and erythrocyte/plasma thiobarbituric acid reactive substance (522 vs 612/33 vs 38 μmol/g Hb/protein) levels were significantly increased, without change in plasma antioxidant status. Nonsignificant changes of advanced oxidation protein products and oxidized LDL were observed. The results provide a solid base for further study of metabolite excretion and antioxidant parameters after ingestion of anthocyanins.
Keywords: Oxidative Stress; cinnamáty; kyselina vanilová; Chromatography, Liquid; oxidační stres; kyseliny kumarové; Humans; Metabolome; Thiobarbituric Acid Reactive Substances; Erythrocytes; Catalase; Glutathione Peroxidase; Female; kyselina benzoová; dospělí; anthokyaniny; lidé; Biomarkers; Antioxidants; glutathionperoxidasa; hydroxybenzoáty; Vanillic Acid; metabolom; antioxidancia; katalasa; Adult; Benzoic Acid; Cinnamates; lipoproteiny LDL; biologické markery; chromatografie kapalinová; ženské pohlaví; Male; Lonicera; hippuráty; Anthocyanins; erytrocyty; ovoce; Hydroxybenzoates; Fruit; Hippurates; Lipoproteins, LDL; Coumaric Acids; mužské pohlaví; hmotnostní spektrometrie; Mass Spectrometry; látky reagující s kyselinou thiobarbiturovou